Taxmans auditing principles and practice 2nd ed. - Sharma S.D. (Tax mann N.D., 2003)
Commerce
UGC X PLAN (2002-2004)
ENGLISH
Keywords: Taxmans auditing principles and practice 2nd ed; Commerce; Commerce